AB0272 The performance of a single centre interventional clinic in early rheumatoid arthritis. (15th June 2017) - Jese, R; Ambrožič, A; Gašperšič, N; Hočevar, A; Pirkmajer, K Perdan; Lestan, B; Pavič, M Nikolič; Novljan, M Plešivčnik; Praprotnik, S; Rotar, Ž; Šipek, A Dolničar; Šuput, D Skvarča; et al.
Abstract : Background: In early rheumatoid arthritis (RA), first assessment by a rheumatologist and/or initiation of disease-modifying anti-rheumatic drugs (DMARD) within 12 weeks of symptom onset are associated with a significant benefit in long-term disease outcome. Objectives: Our objective was to determine the proportion of patients with newly diagnosed RA in whom first rheumatology assessment and/or initiation of DMARD therapy was within the desired time frame. Methods: A retrospective chart review of adult patients diagnosed with RA during years 2014 and 2015 was performed at the rheumatology department of an integrated secondary/tertiary teaching hospital that provides rheumatology services for a population of more than 500.000 residents. Potential cases were identified by searching the electronic medical records for ICD-10 codes M05.* and M06.* Electronic and paper records of patients were then thoroughly reviewed. In addition to demographic and clinical data, dates were recorded for onset of inflammatory joint symptoms, referral to rheumatologist, initial assessment by a rheumatologist and initiation of DMARD therapy. The percentage of patients assessed by a rheumatologist and/or treated with a DMARD within 12 weeks of symptom onset and the median times for delay were then calculated. Results: Between January 1st 2014 and December 31st 2015, 243 new cases of RA were identified at our Department of Rheumatology. Of those, 197 (81.1%) were referred to our early interventional clinic. Within 12 weeks of symptom onset, 111 (45.7%) new RA patients were examined by a rheumatologist and 87 (35.8%) were started on DMARD therapy; the median time from symptom onset to consultation was 13.0 (IQR 4.6–27.8) weeks, median time from referral to consultation was 1 (IQR 1–3) days and median DMARD treatment delay was 15.7 (IQR 8.7–31.9) weeks. Conclusions: 46% of new RA patients were assessed by a rheumatologist and 36% were treated with a DMARD within the recommended time frame of 12 weeks. Most of the treatment delay was due to the time elapsed between symptom onset and referral to a rheumatologist. These results substantiate the efficacy of our early interventional clinic in diagnosing and treating patients with early RA: despite the heavily protracted nationwide waiting times for first rheumatologist assessment and significantly (40%) lower number of rheumatologists per capita compared to European Union average, the percentage of timely treated patients was comparable to recent reports. Disclosure of Interest: None declared